Association Between the Use of Pre- and Post-thrombolysis Anticoagulation With All-Cause Mortality and Major Bleeding in Patients With Pulmonary Embolism - Tan, Jiang-Shan; Liu, Ningning; Hu, Song; Wu, Yan; Gao, Xin; Guo, Ting-Ting; Yan, Xin-Xin; Peng, Fu-Hua; Hua, Lu (Frontiers in Cardiovascular Medicine, 2022)
Objective To explore the comparative clinical efficacy and safety outcomes of anticoagulation before (pre-) or following (post-) thrombolytic therapy in systemic thrombolytic therapy for pulmonary embolism (PE). Methods PubMed, the Cochrane Library, EMBASE, EBSCO, Web of Science, and CINAHL databases were searched from inception through 1 May 2021. All randomized clinical trials comparing systemic thrombolytic therapy vs. anticoagulation alone in patients with PE and those that were written in English were eligible. The primary efficacy and safety outcomes were all-cause mortality and major bleeding, respectively. Odds ratios (OR) estimates and associated 95% confidence intervals (CIs) were calculated. A Bayesian network analysis was performed using R studio software, and then the efficacy and safety rankings were derived. Results This network meta-analysis enrolled 15 trials randomizing 2,076 patients. According to the plot rankings, the anticoagulant therapy was the best in terms of major bleeding, and the post-thrombolysis anticoagulation was the best in terms of all-cause mortality. Taking major bleeding and all-cause mortality into consideration, the most safe–effective treatment was the post-thrombolysis anticoagulation in patients who needed thrombolytic therapy. The net clinical benefit analysis comparing associated ICH benefits vs. mortality risks of post-thrombolysis anticoagulation demonstrated a net clinical benefit of 1.74%. Conclusion The systemic thrombolysis followed by anticoagulation had a better advantage in all-cause mortality and major bleeding than the systemic thrombolysis before anticoagulation. The adjuvant anticoagulation treatment of systemic thrombolytic therapy should be optimized.